The Understanding of Gender Equality in Indonesia by Indonesian Women’s Diaspora in Germany - Supriyatiningsih Wenang; Diyah Nahdiyati; Teti Arndt; Ima Rismawati (Universitas Muhammadiyah Yogyakarta, 2021)
Background: The existence of gender inequality and injustice between men and women may block the national development. Indonesia has experienced an improvement in narrowing the gender gaps, but the challenges are continuous. This study aims to describe the understanding of gender equality and women’s emancipation in Indonesia by Indonesian women’s diaspora in Germany. Methods: A quick survey through an online questionnaire was distributed to 35 Indonesian women’s diaspora in Germany who attended the online dialogue. The questionnaire assessed the characteristics of participants and their understanding of gender equality and women’s emancipation in Indonesia and was analyzed by SPSS. Results: Ninety-four percent of the participants agreed that men and women are a partner and defined gender equality and women’s emancipation as all rights and obligations of women that are equal to men, guaranteed by law, state and religion. Seventy-four percent of the participants saw that the four gender roles in Indonesia are still needed to boost and fight for. Seventy-four percent of the participants agreed that Indonesian women are ready to compete globally as professionals and workers. Conclusion: The majority of participants seemed to have a high awareness of women’s emancipation and gender equality and support to boost women’s gender roles in Indonesia.